Magnesium phosphate ceramics incorporating a novel indene compound promote osteoblast differentiation in vitro and bone regeneration in vivo. (March 2018) - Kim, Ju Ang; Yun, Hui-suk; Choi, Young-Ae; Kim, Jung-Eun; Choi, So-Young; Kwon, Tae-Geon; Kim, Young Kyung; Kwon, Tae-Yub; Bae, Myung Ae; Kim, Nak Jeong; Bae, Yong Chul; Shin, Hong-In; et al.
Abstract: Incorporating bioactive molecules into synthetic ceramic scaffolds is challenging. In this study, to enhance bone regeneration, a magnesium phosphate (MgP) ceramic scaffold was incorporated with a novel indene compound, KR-34893. KR-34893 induced the deposition of minerals and expression of osteoblast marker genes in primary human bone marrow mesenchymal stem cells (BMSCs) and a mouse osteoblastic MC3T3-E1 cell line. Analysis of the mode of action showed that KR-34893 induced the phosphorylation of MAPK/extracellular signal-regulated kinase and extracellular signal-regulated kinase, and subsequently the expression of bone morphogenetic protein 7, accompanied by SMAD1/5/8 phosphorylation. Accordingly, KR-34893 was incorporated into an MgP scaffold prepared by 3D printing at room temperature, followed by cement reaction. KR-34893-incorporated MgP (KR-MgP) induced the expression of osteoblast differentiation marker genes in vitro . In a rat calvaria defect model, KR-MgP scaffolds enhanced bone regeneration and increased bone volume compared with MgP scaffolds, as assessed by micro-computed tomography and histological analyses. In conclusion, we developed a method for producing osteoinductive MgP scaffolds incorporating a bioactive organic compound, without high temperature sintering. The KR-MgP scaffolds enhanced osteoblast activation in vitro and bone regeneration in vivo .